Islamic quality in business and workplace - Aziz@Awang, Nurul Fatma; Sabli, Nurshamimi; Yusop, Rohayu (Universiti Teknologi MARA, Terengganu, 2019)
Islam is a holistic religion . Muslim is encouraged to not only doing goods for achieving success in hereafter, but also to focus on the conduct of the daily activities, of the daily activities. In every action , one should on the relationship with Allah and human being. The religious law in Islam cover all aspects of life such as marriage, health, occupation, business and other social aspects. Despite the comprehensiveness of Islamic teaching, there is a lack of study that relates the religion of Islam and the quality of practice in real life. However, Islam did provide a sturdy foundation on the supposed quality of daily activity especially when handling a business. This is based on a hadith narrated by Sahih Muslim , " Allah loves to see one's task done at the level of "itqan".